Identification of a Novel Chromate and Selenite Reductase FesR in Alishewanella sp. WH16-1 - Zhou, Zijie; Zhu, Lin; Dong, Yixuan; You, Lexing; Zheng, Shixue; Wang, Gejiao; Xia, Xian (Frontiers in Microbiology, 2022)
A ferredoxin protein (AAY72_06850, named FesR) was identified to associate with chromate [Cr(VI)] resistance in Alishewanella sp. WH16-1. FesR and its similar proteins were phylogenetically separated from other reductase families. Unlike the reported Cr(VI) and selenite [Se(IV)] reductases, two 4Fe-4S clusters and one flavin adenine dinucleotide (FAD) -binding domain were found in FesR sequence. The experiment in vivo showed that the mutant strain △fesR had lost partial Cr(VI) and Se(IV) reduction capacities compared to the wild-type and complemented strains. Furthermore, overexpression in E. coli and enzymatic tests in vitro showed FesR were involved in Cr(VI) and Se(IV) reduction. 4Fe-4S cluster in purified FesR was detected by ultraviolet light (UV) spectrum and Electron Paramagnetic Resonance (EPR). The Km values of FesR for Cr(VI) and Se(IV) reduction were 1682 ± 126.2 and 1164 ± 89.41 μmol/L, and the Vmax values for Cr(VI) and Se(IV) reduction were 4.061 ± 0.1431 and 9.427 ± 0.2902 μmol min-1 mg-1, respectively. Additionally, site-directed mutagenesis and redox potential analyses showed that 4Fe-4S clusters were essential to FesR, and FAD could enhance the enzyme efficiencies of FesR as intracellular electron transporters. To the best of our knowledge, FesR is a novel Cr(VI) and Se(IV) reductase.